Abdominal Aortic Aneurysms: Epidemiological, Clinical and Echographic Aspects in The Health Structures of Lomé and At The Kara University Hospital (TOGO) - Machihude PIO; Abalo Mario BAKAI; Bénédict SOUHO; Edabi OTOYI; Kpatekana SIMLAWO; Borgotia D. ATTA; Tchaa TCHEROU; Yaovi Mignazonzon AFASSINOU; Lihanimpo DJALOGUE; D Wiyaou Dieu-Donné KAZIGA; Soulemane PESSINABA (Journal of Hypertension and Cardiology, 2023)
Objective To describe the epidemiological, clinical and arterial Doppler ultrasound aspects of abdominal aortic aneurysm (AAA). Material and Methods This is a prospective study with descriptive and analytical aims carried out from January 2019 to March 2022 (3 years) at the cardiovascular exploration center (CEC)
Keywords: aneurysms